DEGRADACION RUMINAL DE LOS INHIBIDORES DE TRIPSINA DEL FRIJOL (Phaseolus vulgaris) - Raúl Ricalde Velasco; Antonia de la Cruz Morales; José Antonio Martínez García; German D. Mendoza Martínez (Revista Mexicana de Ciencias Pecuarias, 2012)
-